2015
DOI: 10.1016/j.jval.2015.09.1705
|View full text |Cite
|
Sign up to set email alerts
|

Use of Health Services In Brazil: A Systematic Review And Meta-Analysis of Prevalence Studies

Abstract: Medical doctors were more requested than dentists and hospitals. The use of health services was more concentrated in developed areas. The pooled results of meta-analysis suggest representativeness of Brazilian population for the last decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…A systematic review included 659 043 individuals of Brazilian studies and detected a prevalence of 37% of dental visit in the last year, 7 a similar rate to our study. Greater use was observed in individuals with higher income, higher education levels, formal job and health insurance, showing that lower use of dentist services is related to inequities in access.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A systematic review included 659 043 individuals of Brazilian studies and detected a prevalence of 37% of dental visit in the last year, 7 a similar rate to our study. Greater use was observed in individuals with higher income, higher education levels, formal job and health insurance, showing that lower use of dentist services is related to inequities in access.…”
Section: Discussionsupporting
confidence: 87%
“…A systematic review of population-based studies observed an increase in medical and dental consultations from 1998 to 2013 in Brazil countrywide. 7 In the northern—and less developed region—the usage of such health services reduced in this period. Discrepancies in the health services usage in this region may affect the population’s well-being and should be investigated.…”
Section: Introductionmentioning
confidence: 96%
“…Our findings showed an increased underutilization of health services in Manaus Metropolitan Region when compared with the 2013 Brazilian National Health Survey . Despite being higher than expected, the poor performance in this region was likely due to the reduced rate of healthcare services utilization . Individuals from the North and Northeast regions suffer with lower educational attainment, income and have a lower life expectancy at birth .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the Unified Health System (SUS), in its three decades of existence, has increased the life expectancy of Brazilians and improved sanitary indicators, such as access to healthcare, primary healthcare coverage, hospital births, and rates of hospital admission . A pooling of Brazilian surveys conducted until 2013 showed that over 70% of adults visited a doctor in the previous year, while 37% had a dental consultation, with heterogeneity across regions . Inhabitants of the North—and less developed regions—visited doctors and dentists less than individuals living in the Southwest .…”
Section: Introductionmentioning
confidence: 99%
“…Among the attributes of the PHC, the first contact [ 9 ] stands out, defined as “gateway”, which implies accessibility and use of health services by users for each need or problem [ 10 ]. Access refers to the offer, that is, the opportunity or availability of services, and use includes all direct or indirect contact with services, such as consultations, hospitalizations, examinations, and others [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%